Pubic Osteomyelitis in a Combat Training Soldier: A Case Report. Issue 3 (1st March 2017) - Segal, David; Eshed, Iris; Marom, Niv; Gurman, Georgiy; Chen, Jacopo; Nyska, Meir; Mann, Gideon; Yaacobi, Eyal
ABSTRACT: Introduction: Infectious osteomyelitis of the symphysis pubis, known as pubic osteomyelitis is a rare condition with potentially devastating consequences. To the best of our knowledge, this article is the first reported case of a military trainee presenting with pubic osteomyelitis. Materials and Methods: We present a unique case of a patient who simultaneously suffered a combination of local recurrent stress to the symphysis pubis area, and slow-healing multiple palm and finger lacerations which probably acted as distant ports of bacterial entry that concomitantly led to his illness. Results: The patient went through a 6-month period of a complex diagnostic process and an antibiotic treatment with strict activity limitations, after which a full recovery was achieved. Conclusions: Although rare, when treating combat trainees or athletes whose daily life combines extensive physical training and potential ports of entry for bacteria, the treating physician should be aware of the potential for infectious osteomyelitis. Understanding the pathophysiology described would aid physicians when taking the patient history, and conducting an appropriate physical examination. The combination of a relevant history, pubic pain, high fever, and skin lacerations should alert the physician to the possibility of pubic osteomyelitis. When considering prevention, along with a well-designed training course for both soldiers in training camps and athletes, the significance of hygiene and treatment of superficial wounds or skin abrasions cannot be overemphasized.